ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK EKOLOGIS DAN DAMPAKNYA TERHADAP LINGKUNGAN: PERSPEKTIF KONSUMEN DI KOTA PEKANBARU - Ristiyono, Ristiyono; Alwie, Alvi Furwanti; Sulistiyowati, Lilis (Jurnal Tepak Manajemen Bisnis, 2017)
The purpose of this study was to examine the determinants of ecological purchasing decisions. An understanding of these factors is important to know the purchasing decisions of people who can contribute to save the environment. Based on the scale developed from many previous studies, this study Analyzing ecological product purchasing decisions through Perception, Attention On Environment, Consumer Effectiveness, Collectivism, Willingness to Pay More Expensive, interests and actions and their impact on the environment in the City Pekanbaru.Data collected using a questionnaire, then analyzed using SPSS statistical. Research shows Perception, Attention On Environment, Consumer Effectiveness,, Interests and Actions positive effect. Furthermore, environmental concerns affecting the willingness to pay a higher price. Other funding is environmental issues and the effectiveness of the receiving ecological influence purchasing behavior, however, in this study the effects of collectivism and willingness to pay more toward ecological decisions purchese insignificant. Based on these results. Companies can design products and marketing communications program appropriate and in accordance with customer expectations, while for the government, the results of this study can be used as input to determine the policies that can save the environment.